2018
DOI: 10.1080/02667363.2018.1424621
|View full text |Cite
|
Sign up to set email alerts
|

A developing educational psychology service work-allocation model

Abstract: As UK Governments continue with the economic policy of deficit reduction from 2010, many Local Authorities' (LAs) Educational Psychology Services (EPSs) have begun to develop 'traded' models of service delivery in order to maintain jobs and secure services. Nevertheless, EPSs still provide a core service delivery to schools, settings and patches for statutory and prestatutory work which need to be equitably distributed within the team to apportion demands and workloads. This article will provide a detailed des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, in order to retain staff and support motivation, it is suggested that Educational Psychology Services (EPSs) often try to provide EPs with a varied "diet" of work including preventative work, inclusion in local initiatives, individual assessment and consultation, and group work, alongside statutory assessment. In order for this to be achieved, often a short-term solution is needed to meet the demand of statutory assessments in an equitable way (Marsh and Higgins, 2018). It is suggested that EPSs are faced with a dilemma of relying on EPs within the service to focus on statutory assessments, at the expense of other work, or employing costly locums or agency staff to complete the statutory assessments.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to retain staff and support motivation, it is suggested that Educational Psychology Services (EPSs) often try to provide EPs with a varied "diet" of work including preventative work, inclusion in local initiatives, individual assessment and consultation, and group work, alongside statutory assessment. In order for this to be achieved, often a short-term solution is needed to meet the demand of statutory assessments in an equitable way (Marsh and Higgins, 2018). It is suggested that EPSs are faced with a dilemma of relying on EPs within the service to focus on statutory assessments, at the expense of other work, or employing costly locums or agency staff to complete the statutory assessments.…”
Section: Discussionmentioning
confidence: 99%
“…This historical picture (20 + years) broadly aligns with current research (DfE, 2013), with simmilar issues reported. Marsh and Higgins (2018) provide the most recent commentary on service allocation models recommending that 70% of EP time be allocated to 'direct support' such as casework and consultations, 17.5% of time as a exible allocation such as for responding to critical incidences, and 12.5% dedicated to CPD.…”
Section: Introductionmentioning
confidence: 99%
“…EP working-life experiences Sewell et al (UNDER REVIEW) summarised a foundation of existing research exploring EPs' perceptions of their working-life experiences. Most existing studies have examined workload allocation at the service level (DfE, 2023;Imich, 1999;Islam, 2013;Marsh & Higgins, 2018) This literature has shown that most EP work-based time is, or should be, dedicated to 'direct support', including school visits and prepping for school visits (Imich, 1999;Marsh & Higgins, 2018). Within some studies, EPs' perceptions of their workload and work tasks have been explored.…”
Section: Introductionmentioning
confidence: 99%